(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2018)
In the article, the expediency of systematizing the methodology of accounting and supporting of the foreign investments in order to increase the investment attractiveness of the enterprise. Grouped the legal and regulatory framework of the foreign investment process. Highlighted the main elements of foreign investment accounting organization. Presented the advantages of cancelling mandatory state registration of foreign investments. The new Law introduces the principle of state accounting of investments, according to which the submission of statistical reporting on the implementation of foreign investment will be carried out by enterprises with foreign investment and institutions of the bank. The basic rules of the financial and capital investment accounting are identified. Also, are